1967
DOI: 10.1126/science.155.3760.279
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Phylogenetic Trees

Abstract: known responses in the visual system to show typical adaptation properties. This suggests that the site of visual adaptation may be in the bi-polarcell layer, the presumed locus of b-wave generation. Recent electron microscopic studies have demonstrated reciprocal synapses between the bipolar terminals and amacrine processes, and it is suggested that such a ;synaptic arrangement could account for visual adaptation by a mechanism of inhibitory feedback on the bipolar cells. known responses in the visual system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
1,364
1
15

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,318 publications
(1,388 citation statements)
references
References 31 publications
8
1,364
1
15
Order By: Relevance
“…48 Both analyses were made with the software package Phylip. 49 The dendrogram was drawn using TreeView 1.6.6.…”
Section: Resultsmentioning
confidence: 99%
“…48 Both analyses were made with the software package Phylip. 49 The dendrogram was drawn using TreeView 1.6.6.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic relationships among the taxa considered were established using the phylogenetic analysis package PHYLIP (Felsenstein 1989) and the multivariate analysis system NTSYS (Rohlf 1998). For the phylogenetic analysis concerning AFLP allele frequencies in populations or groups of lines, ten independent trees were constructed as described (Heun et al 1997;Badr et al 2000), using CONTML and distance matrix methods (Fitch and Margoliash 1967;Saitou and Nei 1987), and employing various measures of genetic distance (Cavalli-Sforza and Edwards 1967;Nei 1972;Wright 1978;Reynolds et al 1983) calculated from AFLP allele frequency. To cluster single accessions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…c Genetic relationships of domesticated tetraploid wheats with wild T. dicoccoides groups sampled in different regions of the Fertile Crescent with origins already specified in b. Using programs of the PHYLIP package (1993), 10 independent trees were constructed as described (Heun et al 1997;Badr et al 2000) using CONTML (topology shown; Felsenstein 1981) and distance matrix methods (Fitch and Margoliash 1967;Saitou and Nei 1987) employing various measures of genetic distance (Cavalli-Sforza and Edwards 1967;Nei 1972;Wright 1978;Reynolds et al 1983) calculated from AFLP allele frequencies between groups of lines from the geographic regions indicated. The number of tree-buiding methods generating the same topologies is indicated at branches.…”
Section: Resultsmentioning
confidence: 99%
“…Trees of the RecA sequences were generated using two parsimony methods (the protpars program in PHYLIP and the heuristic search algorithm of PAUP) and three distance methods (the least-squares method of De Soete (De Soete 1983) as implemented in GDE, and the Fitch-Margoliash (Fitch and Margoliash 1967) and neighbor-joining methods (Saitou and Nei 1987) as implemented in PHYLIP). Trees of the SS-rRNA sequences were generated using one parsimony method (the dnapars algorithm of PHYLIP) and the same three distance methods as used for the RecA trees.…”
Section: Phylogenetic Treesmentioning
confidence: 99%